Friction and Wear Characteristics of MoS2-based Solid-lubricated Bearings in Vacuum Atmosphere - Liu Zhaolin; Zhang Zhanli; Li Hongliang; Xiao Yan; Tang Yuanchao; Wang Jian (Jixie chuandong)
The friction and wear characteristics of MoS2-based solid-lubricated bearings have an important influence on the performance and wear life of bearings in vacuum atmosphere. Relying on the vacuum ball-friction and wear testing machines and based on the quasi-statics of rolling bearings and the Archard wear theory, the wear life model of solid lubricated bearings is established and verified by experiments. Numerical simulation method is used to study the influence of working condition parameters and bearing structure parameters on the friction and wear characteristics of the solid-lubricated bearings. The model can predict the wear life of the bearings well, and the error between the calculated results and the experimental results is within 11.7%. In the low speed range, the wear life of the solid-lubricated bearings under axial load has no relation with the rotation speed, but the load has a great influence on the wear life, showing a negative correlation trend. The change of radius coefficient of inner and outer ring grooves directly affects the wear life of bearings, and it increases with the increase of radius coefficient of inner ring grooves and decreases with the increase of radius coefficient of outer ring grooves. The increasing number of bearing steel balls and the enlargement of the contact angle can effectively reduce the wear rate of bearings and improve the wear life of bearings.